Polysiloxanes Modified by Thiol‐Ene Reaction and Their Interaction with Gold Nanoparticles. Issue 11 (23rd October 2019) - Lemonier, Stéphane; Marty, Jean‐Daniel; Fitremann, Juliette
Abstract: A poly(vinylmethyl‐co‐dimethyl)siloxane has been functionalized with phenylethanethiol, N‐methylmercaptoacetamide and heptadecafluoro‐1‐decanethiol by a thermal radical thiol‐ene reaction initiated by azobisisobutyronitrile. The resulting polymers were obtained in good yields with most of the time a complete conversion of the vinyl groups. The reaction also preserved the fragile polysiloxane backbone. The polymer, grafted with about 25 % of mercapto‐acetamide groups is soluble in polar solvents such as dimethylformamide and dimethyl sulfoxide, opening the way for further functionalization with polar molecules such as unprotected carbohydrates. Spherical and branched gold nanoparticles were coated with these polymers. This coating induced a surface resonance plasmon shift resulting from the interaction of the grafted polysiloxanes with the nanoparticle surface. The shift can be explained by the variation of the refractive index of the side groups but may be also related to the self‐organization of polysiloxanes and their interactions with the gold surface depending on their polarity. Abstract :